Optimalisasi Sistem Proporsional Terbuka Melalui Perubahan Parlemen Threshold - Prayugo, Arlis (Indonesian Journal Publisher, 2025)
This study examines the implementation of the 4% parliamentary threshold in Indonesia’s electoral system and its implications for proportionality and political representation. The Constitutional Court’s ruling on this regulation has sparked debates, as it is considered to contradict the principles of popular sovereignty, electoral fairness, and legal certainty. This research aims to evaluate the extent to which the parliamentary threshold aligns with democratic principles and contributes to the effectiveness of the party system. Employing a qualitative descriptive method, this study relies on legal provisions, official documents, and academic literature related to electoral laws and proportional representation.The findings indicate that, while the parliamentary threshold aims to streamline the party system, it often results in wasted votes, undermining the proportional nature of elections. Smaller or emerging parties are disproportionately affected, limiting their ability to represent their constituents effectively. This exclusion diminishes political inclusivity and restricts voter choices. Therefore, revising the parliamentary threshold is essential to balancing party system efficiency with fair political representation. Adjustments to the threshold would help reduce wasted votes, enhance electoral integrity, and strengthen public trust in the democratic process. A more inclusive electoral framework is necessary to uphold fairness and ensure that all political voices are adequately represented in Indonesia’s democracy.